The expression 5(2a-b)-3(5b-6a) has to be simplified.

5(2a-b)-3(5b-6a) B) 4(2-x)-3(-5-12x)

= 10a - 5b - 15b + 18a

= 28a - 20b

Similarly, 4(2-x)-3(-5-12x) = 8 - 4x + 15 + 36x = 23 + 32x

** The simplified form of 5(2a-b)-3(5b-6a) = 28a - 20b and 4(2-x)-3(-5-12x) = 23 +...**

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The expression 5(2a-b)-3(5b-6a) has to be simplified.

5(2a-b)-3(5b-6a) B) 4(2-x)-3(-5-12x)

= 10a - 5b - 15b + 18a

= 28a - 20b

Similarly, 4(2-x)-3(-5-12x) = 8 - 4x + 15 + 36x = 23 + 32x

**The simplified form of 5(2a-b)-3(5b-6a) = 28a - 20b and 4(2-x)-3(-5-12x) = 23 + 32x**